Komposisi Kimia Pakan Ikan Nila (Oreochromis niloticus) Berbasis Tepung Bulu Ayam dan Tepung Daun Kelor dengan Penambahan Kunyit sebagai Fitobiotik - Andi Pernanda; Tusaban Tusaban; Dewi Shinta Achmad; Nur Jihan Fareranty Piu (Pusat Riset dan Inovasi Nasional, 2026)
The use of local raw materials in Nile tilapia feed formulation needs to be developed to reduce dependence on increasingly expensive conventional feed ingredients. This study aimed to analyze the effect of different formulations of chicken feather meal and moringa leaf meal with turmeric addition as a phytobiotic on the chemical composition of Nile tilapia (Oreochromis niloticus) feed. The study used a completely randomized design with three treatments and three replications. P1 consisted of 55% chicken feather meal, 25% moringa leaf meal, 5% turmeric, 10% corn flour, and 5% starch; P2 consisted of 40% chicken feather meal, 40% moringa leaf meal, 5% turmeric, 10% corn flour, and 5% starch; and P3 consisted of 25% chicken feather meal, 55% moringa leaf meal, 5% turmeric, 10% corn flour, and 5% starch. The parameters analyzed were crude protein, moisture, ash, crude lipid, crude fiber, and carbohydrate. Data were analyzed using analysis of variance followed by the least significant difference test when significant differences occurred. The results showed that P3 produced the highest protein content (22.60%), ash content (6.65%), crude fiber (6.55%), and carbohydrate (8.45%), whereas P2 produced the highest lipid content (6.54%). Based on chemical analysis, P3 was the most prominent formulation for most proximate parameters. However, this formulation cannot be directly concluded as the best feed for fish growth because digestibility, palatability, feed conversion ratio, growth, survival, and health responses were not evaluated. Further biological testing is therefore required to confirm its feasibility for Nile tilapia culture.